Greater apathy is associated with faster rate of cognitive decline in older adults with type 2 diabetes: Neuropsychiatry and behavioral neurology/Assessment/Measurement of neuropsychiatric/Behavioral and psychological symptoms. (7th December 2020) - Soleimani, Laili; Ravona‐Springer, Ramit; Lin, HungMo; Liu, Xiaoyu; Sano, Mary; Heymann, Anthony; Beeri, Michal Schnaider
Abstract: Background: Although depression is known to be highly associated with cognitive impairment and dementia, it is unclear how its different dimensions affect cognition. Here, we examined the relationships between baseline dimensions of depression with cognitive decline in a sample of initially non‐demented older adults with type 2 diabetes (T2D) participating in the Israel Diabetes and Cognitive Decline (IDCD) study. Methods: Subjects [n=1023; mean age= 71.6 (SD= 4.6); 41.1% female] completed the 15‐item geriatric depression scale (GDS) at baseline and a neuropsychological battery approximately every 18 months. Cognitive domains included episodic memory, attention/working memory, executive functions, and language/semantic categorization. Global cognition was the average of the four domains z‐scores. The GDS dimensions were defined as Dysphoric Mood, Withdrawal–Apathy–Vigor (WAV), Anxiety, Hopelessness and Memory Complaint, based on previous studies. Mixed regression models adjusting for age, sex, and education assessed associations of baseline depression dimensions with cognitive decline. Results: Cross‐sectionally, there were numerous associations between depression dimensions and cognitive outcomes (Table 1). Overtime, WAV was significantly associated with greater decline in global cognition (p=0.004), executive function (p=0.002) and episodic memory (p=0.039). Dysphoric mood was associated with a faster rate of episodic memory decline (p=0.022). Anxiety was not associated with neither cross sectional nor longitudinal cognitive outcomes. Adjusting for cardiovascular risk factors did not alter substantively the results. Conclusion: Similar to non‐diabetic populations, different dimensions of depression in T2D elderly were associated with variable cognitive outcomes. Longitudinally, among the aspects of depression, apathy was consistently associated with greater rate of cognitive decline. This highlights the possibility of shared mechanisms between depression and dementia, an example of which could be cerebral microvascular disease, which is highly prevalent in T2D patients.